Conocemos el diccionario y su utilidad - Infante Tejada, Edwin (2019)
This sufficiency work has been prepared for students of the first grade of Secondary Education of the city of Trujillo in the year 2019, with the theme entitled: We know the dictionary and its usefulness, in which everyday situations have been taken into account in the that students daily use a dictionary as a query of words or unknown terms for their vocabulary establish interpersonal relationships observing that they have different characteristics and qualities._x000D_ In the elaboration of the session, we worked with the pedagogical and didactic processes of the Communication area to promote expected and significant learning._x000D_ The strategies used were designed to promote the active and meaningful participation of all students._x000D_ It is intended at all times to awaken the interest and motivation of the student in the area of Communication, since it is a very important and valuable area